Imaging study of using radiopharmaceuticals labeled with cyclotron-produced 99mTc. (2nd November 2016) - Hou, X; Tanguay, J; Vuckovic, M; Buckley, K; Schaffer, P; Bénard, F; Ruth, T J; Celler, A
Abstract: Cyclotron-produced 99m Tc (CPTc) has been recognized as an attractive and practical substitution of reactor/generator based 99m Tc. However, the small amount of 92-98 Mo in the irradiation of enriched 100 Mo could lead to the production of other radioactive technetium isotopes (Tc-impurities) which cannot be chemically separated. Thus, these impurities could contribute to patient dose and affect image quality. The potential radiation dose caused by these Tc-impurities produced using different targets, irradiation conditions, and corresponding to different injection times have been investigated, leading us to create dose-based limits of these parameters for producing clinically acceptable CPTc. However, image quality has been not considered. The aim of the present work is to provide a comprehensive and quantitative analysis of image quality for CPTc. The impact of Tc-impurities in CPTc on image resolution, background noise, and contrast is investigated by performing both Monte-Carlo simulations and phantom experiments. Various targets, irradiation, and acquisition conditions are employed for investigating the image-based limits of CPTc production parameters. Additionally, the relationship between patient dose and image quality of CPTc samples is studied. Only those samples which meet both dose- and image-based limits should be accepted in future clinical studies.